Probiotic VSL#3 Treatment Reduces Colonic Permeability and Abdominal Pain Symptoms in Patients With Irritable Bowel Syndrome - Boonma, Prapaporn; Shapiro, Jordan M.; Hollister, Emily B.; Badu, Shyam; Wu, Qinglong; Weidler, Erica M.; Abraham, Bincy P.; Devaraj, Sridevi; Luna, Ruth Ann; Versalovic, James; Heitkemper, Margaret M.; Savidge, Tor C.; et al. (Frontiers in Pain Research, 2021)
Background: Little is known regarding the clinical impact of treatment and treatment duration of probiotic VSL#3 on gut and microbiome function in irritable bowel syndrome (IBS). As part of a safety trial, we assessed the effect of VSL#3 treatment duration on abdominal pain, stooling, gut permeability, microbiome composition and function. Methods: Adults with IBS were randomized into an open label trial to receive the probiotic VSL#3 for 4 or 8 weeks. Adverse events, abdominal pain, and stooling patterns were recorded daily. Gut permeability, fecal bile acid levels, and microbiome composition were profiled at baseline and after treatment. Results: Fifteen subjects completed the trial (4-week: n = 8; 8-week: n = 7). Number of pain episodes decreased in both groups (P = 0.049 and P = 0.034; 4- vs. 8-week, respectively). Probiotic organisms contained in VSL#3 were detected in feces by whole shotgun metagenomic sequencing analysis and relative abundances of Streptococcus thermophilus, Bifidobacterium animalis, Lactobacillus plantarum, and Lactobacillus casei subsp. paraccasei correlated significantly with improved abdominal pain symptoms and colonic permeability at study completion. Although abdominal pain correlated significantly with the detection of probiotic species at study completion, a composite view of gut microbiome structure showed no changes in community diversity or composition after VSL#3 treatment. Conclusions: Probiotic organisms identified in stool correlated significantly with improvement in colonic permeability and clinical symptoms, prompting future studies to investigate the mechanistic role of VSL#3 and colonic permeability in IBS pathophysiology in a larger randomized controlled trial. Clinical Trial Registration:www.clinicaltrials.gov, Identifier: NCT00971711.